The effect of different light treatments on nutrient concentration and leaf exchange in Brassica Chinensis - Harun, Ahmad Nizar; Ahmad, Robiah; Mohamed, Norliza; Abdul Rahim, Abd Rahman; Khan, Sheroz (Institute of Electrical and Electronics Engineers Inc., 2019)
The effect of different LED light treatments on nutrient concentration and leaf gas exchange in Brassica chinensis was performed in this study utilizing Internet of Things (IoT) technology as remote monitoring system. Brassica chinensis were grown under four different light treatments and have been used as light source. The experiments were conducted namely T1 (continues light; 24 h lights), T2 (pulse lights: 1 h lights 15 minutes darks), T3 (various light intensities) and T4 (continues lights + Far red). The observation of nutrient concentration and activity leaf gas exchange plants were analyzed. An intelligent system using embedded system has been developed to automate the LED control and manipulation. The system is able to analze on data and monitor the environmental parameters of the plant factory on line via internet. The result shows that the system is stable and has a significant referential in the area of plant factory or indoor farming system. Based on the overall result, Continues Light (CL) gave a high impact towards Brassica chinensis growth. Therefore, combination CL and Far red also enhanced the plant nutrient concentration and the activity of leaf gas exchange.